2013
DOI: 10.1194/jlr.m037176
|View full text |Cite
|
Sign up to set email alerts
|

PAF enhances MMP-2 production in rat aortic VSMCs via a β-arrestin2-dependent ERK signaling pathway

Abstract: Platelet-activating factor (PAF), 1-O-alkyl-2-acetyl-sn-glycero-3-phosphocholine, is a potent phospholipid mediator and has been reported to be localized in atherosclerotic plaque. However, its role in the progression of atherosclerosis remains unclear. In the present study, we investigated the role of PAF in the production of matrix metalloproteinase (MMP) in primary vascular smooth muscle cells (VSMCs). When rat aortic primary VSMCs were stimulated with PAF (1 nmol/l), the expressions of MMP-2 mRNA and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…34 Other cytokines, including platelet-activating factor and IL-1b, have been implicated in MMP-2 expression in rat aortic smooth muscle cell via ERK activation. 35,36 Additionally, through ERK phosphorylation, Ang II also induces the expression of platelet-derived growth factor B-chain in rat ASMCs. 37 p38 MAPK and JNK do not appear to be involved in Ang II-induced MMP-2 upregulation in HASMCs (data not shown) because Ang II does not induce p38 MAPK and JNK phosphorylation (Figure 4a and c).…”
Section: Discussionmentioning
confidence: 99%
“…34 Other cytokines, including platelet-activating factor and IL-1b, have been implicated in MMP-2 expression in rat aortic smooth muscle cell via ERK activation. 35,36 Additionally, through ERK phosphorylation, Ang II also induces the expression of platelet-derived growth factor B-chain in rat ASMCs. 37 p38 MAPK and JNK do not appear to be involved in Ang II-induced MMP-2 upregulation in HASMCs (data not shown) because Ang II does not induce p38 MAPK and JNK phosphorylation (Figure 4a and c).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that the effects of TQ involved mitochondria-dependent apoptosis pathway.Vascular smooth muscle cell migration and secretion of various extracellular matrix (ECM) proteins (mainly MMP2 and MMP9) by macrophages also contribute to the vascular remodelling 27. Furthermore, the release of MMP2 and MMP9 promotes VSMC proliferation and migration 28,29. TQ decreased migration and invasion, as well as the expression of MMP9 and MMP2 in A549 cells and human glioblastoma cells 30,31.…”
mentioning
confidence: 99%
“…A number of ADAMs (disintegrin metalloproteinases) containing an MMP-like catalytic domain, such as ADAM-10, ADAM-15, and ADAM-17 are also expressed in vascular cells [ 75 ]. It was shown that agonist stimulation of platelet-activating factor receptor (PAFR) belonging to GPCR family enhanced MMP-2 production in rat aortic primary vascular SMCs via the activation of a β-arrestin-dependent ERK signaling pathway [ 76 ]. PAF-induced MMP-2 production was significantly attenuated by ERK inhibition using molecular and pharmacological inhibitors suggesting that ERK signaling pathway is important for PAF-induced MMP-2 production in vascular SMCs.…”
Section: Discussionmentioning
confidence: 99%